2022
DOI: 10.15376/biores.17.2.3332-3344
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic water penetration behavior of top coating color and its effects on structure properties of double-coated layer

Abstract: The relationship between the dynamic water penetration behavior of top coating color and double-coated paper properties, including pore structure, surface roughness, gloss, and surface latex content, was investigated. Top coating was applied onto the precoated paper prepared using different pigment types, thereby having different pore structures. To investigate the effect of dwell time on pore structure and surface latex content, coating speed and the distance between two coating heads of a laboratory coater w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, dynamic water absorption of the top-coating color increased with the increase of the number of pores in the pre-coated layer. Accordingly, the surface latex concentration of the top-coated layer decreased with the increases in the water penetration rate of the topcoating color into the pre-coated layer (Im et al 2022). Thus, the increase in the mottle index of double-coated paper can be attributed to the uneven distribution of latex in the coated paper, depending on the type of pre-coating pigment used.…”
Section: Effect Of the Type Of Pre-coating Pigment On Print Mottlementioning
confidence: 96%
See 3 more Smart Citations
“…Furthermore, dynamic water absorption of the top-coating color increased with the increase of the number of pores in the pre-coated layer. Accordingly, the surface latex concentration of the top-coated layer decreased with the increases in the water penetration rate of the topcoating color into the pre-coated layer (Im et al 2022). Thus, the increase in the mottle index of double-coated paper can be attributed to the uneven distribution of latex in the coated paper, depending on the type of pre-coating pigment used.…”
Section: Effect Of the Type Of Pre-coating Pigment On Print Mottlementioning
confidence: 96%
“…In a previous study (Im et al 2022), it was found that the number of pores per unit area at the surface of the coating layer was affected by the dwell time, which is the time between the rod and metering of the surplus coating color. Especially, the increase in dwell time during the pre-coating stage significantly increased the number of pores per unit area at the double-coated layer surface compared to the changes in dwell time during the topcoating.…”
Section: Effect Of the Dwell Time On Print Mottlementioning
confidence: 99%
See 2 more Smart Citations